Polymorphisms in F2, F7, and PAI1 genes in men with coronary atherosclerosis - E. V. Stryukova; V. N. Maksimov; Ya. V. Polonskaya; I. S. Murashov; A. M. Volkov; A. V. Kurguzov; A. M. Chernyavsky; E. V. Kashtanova (Российский кардиологический журнал)
Aim. To study the associations of polymorphisms in F2, F7, and PAI1 genes with the presence of vulnerable plaque in coronary arteries (CA) and the blood concentration of proteins encoded by these genes.Material and methods. The study included 101 men 40-70 years old with documented coronary atherosclerosis, who underwent coronary artery bypass grafting. According to the histological analysis of atherosclerotic plaques, men were divided into 2 groups: 40 men (39,6%) with stable plaque; 61 men (60,4%) with vulnerable plaques in CA. Genotyping of rs1799963 and rs6046 was performed by reverse transcription polymerase chain reaction, rs1799889 — by polymerase chain reaction. Statistical processing was performed using the SPSS 16.0 software package.Results. In patients with stable plaques, allele A of rs6046 polymorphism in the F7 gene was observed in 2,9 times more often (95% confidence interval (CI), 1,20-7,20, p=0,021) than in men with vulnerable plaques. The odds ratio of the GA genotype carriage is 4,03 times higher among patients with stable plaques in CA compared with vulnerable plaques (95% CI, 1,49-10,93, p=0,006). The odds ratio of the 5G/4G genotype carriage among patients with stable plaques in CA is 2,47 times higher than in patients with vulnerable plaques (95% CI, 1,08-5,62, p=0,039). The 4G/4G genotype carriage is 5,85 times much more common in men with stable plaques (95% CI, 1,61-21,34, p=0,003).Conclusion. Polymorphism in the PAI1 (rs1799889) and F7 (rs6046) genes are associated with the presence of vulnerable plaques in CA in men with verified coronary atherosclerosis. There were no differences between the groups in the frequencies of genotypes and alleles of the rs1799963 polymorphism of the F2 gene. Also, no significant differences were found in the blood levels of PAI-1 and factor VII in groups with different genotypes.